DNA metabarcoding analysis of three material types to reveal Joro spider (Trichonephila clavata) trophic interactions and web capture - Grabarczyk, Erin E.; Querejeta, Marina; Tillman, P. Glynn; Wallace, Rebekah D.; Barnes, Brittany F.; Meinecke, Colton D.; Villari, Caterina; Gandhi, Kamal J. K.; LaForest, Joseph; Elliott, Matt; Schmidt, Jason M. (Frontiers in Ecology and Evolution, 2023)
Introduced species alter established trophic interactions and molecular analysis can resolve changes in community structure and associated foraging links. Joro spiders (Trichonephila clavata) were recently introduced to the United States and their range is rapidly expanding across the east coast. Here, we used DNA metabarcoding of fecal samples, prey remains from webs, and dissected guts to compare diet composition of female Joro spiders in the southeastern United States. We amplified DNA from three material types using arthropodtargeted COI primers and sequenced with IIlumina MiSeq. Prey remains from webs had the highest diversity, richness, as well as the highest proportion of prey reads relative to Joro spider reads. Recovery of prey reads from fecal samples and dissected gut content was low and both were overwhelmed by Joro spider DNA. Although fecal samples and gut content had high proportions of Joro spider reads, fecal samples had higher prey diversity and richness.Moreover, we detected prey DNA from fecal samples several days after capture from the field, which reveals initial gut retention time estimates for fecal samples collected from web-building spiders. Combined, our results offer a first glimpse at the complexity of trophic associations for an introduced web-building spider and identify a viable material, prey remains from webs, as a source of prey DNA for estimates of biodiversity associated with web-building spiders.